Pelaksanaan Pembelajaran Sejarah Menggunakan Media Komik Berbasis Digital di SMK Negeri 1 Gunung Talang - Suryadi Fajri; Desi Indriani (UIN Imam Bonjol Padang, 2022)
The application of media in the learning process is very enjoyable so as to create an effective and efficient learning atmosphere. This is the background of the research on the implementation of Digital-Based Comic Media which was carried out at SMK Negeri 1 Gunung Talang. Comic media is a fun reading material because it has lots of pictures and is explained with various characters of someone who participates in acting out the story. The research objectives include knowing the planning and implementation of digital-based comic media in history learning. Preparation of research using qualitative research methods with a qualitative descriptive approach. The type of research used is field research to look specifically at data about the Implementation of History Learning Using Digital-Based Comic Media. The informants in this study were school principals, history teachers, and students at SMK Negeri 1 Gunung Talang. From the results of research in the field, it can be obtained the results of the research that in the process of implementing digital-based comic media learning, it has been carried out starting from the lesson plans prepared by the teacher such as learning devices and learning materials and media. The implementation of history learning using digital-based comic media can run well, but there are some problems such as the lack of facilities and infrastructure, the duration of time is too short, the media used is still simple. Keywords: History learning, learning media, Digital-Based Comics.